2016
DOI: 10.5492/wjccm.v5.i2.121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prone position in acute respiratory distress syndrome patients: A pathophysiology-based review

Abstract: Acute respiratory distress syndrome (ARDS) is a syndrome with heterogeneous underlying pathological processes. It represents a common clinical problem in intensive care unit patients and it is characterized by high mortality. The mainstay of treatment for ARDS is lung protective ventilation with low tidal volumes and positive end-expiratory pressure sufficient for alveolar recruitment. Prone positioning is a supplementary strategy available in managing patients with ARDS. It was first described 40 years ago an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 160 publications
1
123
0
20
Order By: Relevance
“…There are also a number of risk factors for the occurrence of ALI, including inflammation, infection, multiple transfusions, sepsis, smoke inhalation, pneumonia, acute pancreatitis, near‐drowning aspiration of gastric contents, and severe trauma . Currently, the only method of treatment for lung diseases is the use of lung protective ventilation with positive end‐expiratory pressure and low tidal volumes, as there is insufficiency in pharmacological therapies for preventing injury or promoting repair . Although there have been a number of therapeutic interventions recognized over the past couple of years, the occurrence of ALI cases has increased from approximately 1.5 to 75 cases per a 100 000 population, while the mortality of patients diagnosed with ARDS has reached 40% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a number of risk factors for the occurrence of ALI, including inflammation, infection, multiple transfusions, sepsis, smoke inhalation, pneumonia, acute pancreatitis, near‐drowning aspiration of gastric contents, and severe trauma . Currently, the only method of treatment for lung diseases is the use of lung protective ventilation with positive end‐expiratory pressure and low tidal volumes, as there is insufficiency in pharmacological therapies for preventing injury or promoting repair . Although there have been a number of therapeutic interventions recognized over the past couple of years, the occurrence of ALI cases has increased from approximately 1.5 to 75 cases per a 100 000 population, while the mortality of patients diagnosed with ARDS has reached 40% .…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, the only method of treatment for lung diseases is the use of lung protective ventilation with positive end-expiratory pressure and low tidal volumes, as there is insufficiency in pharmacological therapies for preventing injury or promoting repair. 6,7 Although there have been a number of therapeutic interventions recognized over the past couple of years, the occurrence of ALI cases has increased from approximately 1.5 to 75 cases per a 100 000 population, while the mortality of patients diagnosed with ARDS has reached 40%. 8,9 Based on this information, urgency in in discovering newer and more accurate biomarkers is imminent in order to help provide a better diagnosis along with a positive prognosis of ALI.…”
mentioning
confidence: 99%
“…iNO (20 ppm) was initiated; and dobutamine was replaced with milrinone (0.5 mcg/kg/min) due to increased pulmonary artery outlet pressure. The child was placed in prone position due to refractory ARDS for the initial 12-hour period, according to current recommendations reviewed by Koulouras et al 4 On the fifth day of evolution, with no clinical improvement, methylprednisolone was used as an adjuvant measure at a dose of 4 mg/kg/day and maintained for 48 hours. Respiratory acidosis and hypoxemia persisted, with average arterial oxygen saturation (SatO 2 ) of 77% and pCO 2 >100 mmHg, radiological worsening, and bilateral interstitial pulmonary veiling.…”
Section: F I G U R E 1 E X T E N S I V E P N E U M O N I a W I T H mentioning
confidence: 99%
“…The survival benefit of prone positioning was confirmed in the PROSEVA study in 2013 [12] showed decreased 28-day and 90-day mortality and increased ventilator-free day only if the patients had fair lung protective strategy and longer prone positioning duration. The mechanisms of improvement oxygenation including making more homogenous ventilation, decreasing ventilationperfusion mismatch, avoiding ventilator induced lung injury, and decreasing compression by heart or abdomen [13].…”
Section: Introductionmentioning
confidence: 99%